2010
DOI: 10.1534/genetics.109.111419
|View full text |Cite
|
Sign up to set email alerts
|

Ssz1 Restores Endoplasmic Reticulum-Associated Protein Degradation in Cells Expressing Defective Cdc48–Ufd1–Npl4 Complex by Upregulating Cdc48

Abstract: The endoplasmic reticulum (ER)-associated protein degradation (ERAD) pathway eliminates aberrant proteins from the ER. The key role of Cdc48p-Ufd1p-Npl4p is indicated by impaired ERAD in Saccharomyces cerevisiae with mutations in any of this complex's genes. We identified SSZ1 in genetic screens for cdc48-10 suppressors and show that it upregulates Cdc48p via the pleiotropic drug resistance (PDR) network. A pSSZ1 plasmid restored impaired ERAD-M of 6myc-Hmg2 in cdc48-10, ufd1-2, and npl4-1, while SSZ1 deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Indeed, HAC1 splicing was elevated in untreated ∆rpn4 cells, consistent with high throughput data ( Figure 3C; Jonikas et al, 2009). The activation of the UPR in the absence of Rpn4 likely arises from inefficient ERAD and a subsequent buildup of misfolded proteins in the ER (Ng et al, 2000;Bosis et al, 2010). Accordingly, constitutive UPR signaling in ∆rpn4 cells was similar to that in cells lacking the ubiquitin ligase Hrd1, which is essential for ERAD.…”
Section: Rpn4 and The Upr Cooperate To Counteract Er Stresssupporting
confidence: 80%
See 1 more Smart Citation
“…Indeed, HAC1 splicing was elevated in untreated ∆rpn4 cells, consistent with high throughput data ( Figure 3C; Jonikas et al, 2009). The activation of the UPR in the absence of Rpn4 likely arises from inefficient ERAD and a subsequent buildup of misfolded proteins in the ER (Ng et al, 2000;Bosis et al, 2010). Accordingly, constitutive UPR signaling in ∆rpn4 cells was similar to that in cells lacking the ubiquitin ligase Hrd1, which is essential for ERAD.…”
Section: Rpn4 and The Upr Cooperate To Counteract Er Stresssupporting
confidence: 80%
“…Indeed, Yap1 not only activates RPN4 but is itself activated by Rpn4 (Mannhaupt et al, 1999) and may aid stress resistance by preventing oxidative damage. Furthermore, we directly tested the Rpn4 target gene CDC48 (Bosis et al, 2010), even though it was not found in the screen. Overexpression of CDC48 also restored growth of ∆hac1 cells expressing ngCPY*, although weakly compared to overexpression of RPN4 (Figures 2B -E).…”
Section: A Screen For Genes Promoting Er Stress Resistance In Upr Mutmentioning
confidence: 99%
“…The Zuo1-binding and nucleotide-binding domains could be eliminated individually, but Ssz1 is nonfunctional if both domains are disrupted in cis, suggesting that at least one intact domain is necessary for function. Independent of its roles in the ribosome, Ssz1 has been shown to activate Pdr1, a transcription factor associated with the induction of genes involved in the efflux of cytotoxic compounds, the stress response, lipid metabolism, and the ERassociated degradation (ERAD) pathway (33). Ssb is thought to be involved primarily in cotranslational protein folding and the promotion of nascent-chain movement through the exit tunnel.…”
Section: Hsp70 and Cofactorsmentioning
confidence: 99%
“…In fact, genetic evidence indicates that ERAD-M substrates are most sensitive to Cdc48 depletion [115], and p97 dependence correlates with the relative stability of a polytopic membrane protein in the bilayer [116]. In contrast, some ERAD substrates are retrotranslocated in a Cdc48/p97-independent fashion and instead use an analogous AAA complex in the proteasome cap [117-120].…”
Section: Er Associated Degradation: a Quick-fix For Misfolded Proteinmentioning
confidence: 99%